Feasibility and outcomes of PCI with novel tapered coronary stent in people living with HIV: A prospective, single-center study with literature review - H.S. Natraj Setty; B.H. Natesh; M.C. Yeriswamy; V.A. Sathwik Raj; Rahul S. Patil; H.B. Chetan Kumar; L. Sridhar Shastry; B.C. Srinivas; Babu Reddy; Jayashree Kharge; C.M. Nagesh; S. Manohar; et al. (Indian Heart Journal)
Background and objective: Patients with chronic HIV infection face a high risk of premature coronary atherosclerosis, partly due to continuous HAART therapy and susceptibility to opportunistic infections, complicating percutaneous coronary intervention (PCI). HIV patients have unique coronary vasculature characteristics. This study aimed to assess the clinical outcomes of PCI using the novel tapered sirolimus-eluting coronary stent (SES) system in HIV patients. Methods: A prospective, single-arm, non-randomized study was conducted at a tertiary cardiac care center, including 15 HIV-positive patients with acute coronary syndromes. PCI was performed using the study device for de novo coronary lesions with significant size disparity between reference vessel segments. The cumulative incidence of major adverse cardiovascular events (MACE), defined as cardiac death, myocardial infarction, and clinically driven target-lesion revascularization (CD-TLR), was the primary endpoint. Results: Since 2018, 15 HIV-positive patients with a mean age of 50.67 years underwent PCI with the study device. Despite cardiac risk factors and complex lesions, 100 % procedural and device success was achieved by restoring myocardial flow (TIMI flow III). Over a median follow-up of 40 months, no MACE or adverse events were recorded. Conclusions: This study provides new evidence on the use of the long, tapered SES for treating HIV-positive patients, demonstrating high success rates and favorable long-term outcomes. It is the first report of such outcomes using a long, tapered SES in this population.